2021
DOI: 10.18502/ijps.v16i3.6252
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Mindfulness-Based Cognitive Therapy and Cognitive Behavioral Therapy for Anxiety, Depression, and Fatigue in Cancer Patients: A Randomized Clinical Trial

Abstract: Objective: Cancer is associated with some psychological problems that play an important role in the severity and continuity of cancer. Cancer may lead to maladaptive psychological reactions such as anxiety, depression, and fatigue. Depression and anxiety are highly prevalent in cancer patients. This study aimed to compare the efficacy of mindfulness-based cognitive therapy (MBCT) and cognitive behavioral therapy (CBT) for anxiety, depression, and fatigue in cancer patients. Method: The present study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
0
10
1
Order By: Relevance
“…Thereafter, 2012 articles were further removed by browsing the titles and abstracts. Finally, 15 articles were included after full-text reading, including 13 quantitative analyses [37][38][39][40][41][42][43][44][45][46][47][48][49] and 2 qualitative analyses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereafter, 2012 articles were further removed by browsing the titles and abstracts. Finally, 15 articles were included after full-text reading, including 13 quantitative analyses [37][38][39][40][41][42][43][44][45][46][47][48][49] and 2 qualitative analyses.…”
Section: Resultsmentioning
confidence: 99%
“…The sample size ranged from 29 to 294, with 1979 cases. Of the included articles, seven reported on patients with breast cancer 37,38,[42][43][44]50,51 , one on patients with melanoma 47 , five on patients with mixed cancers 39,46,48,52,53 , one on patients with laryngeal squamous cell carcinoma 49 and one on patients with head and neck cancer 54 . The average age of the participants ranged from 37.45 to 59.7 years.…”
Section: Figurementioning
confidence: 99%
“…Exceptions to this are five well-designed studies that compared an MBI to supportive-expressive group therapy, 144,145 psychoeducation, 146 or cognitive behavioral therapy. 60 Effect sizes favoring the MBI in these studies are typically smaller than those with a usual care or waitlist control (in the 0.3 range), but still show significantly greater improvements in anxiety in the MBI groups over active control.…”
Section: Recommendationsmentioning
confidence: 72%
“…141 Thus, the benefits of yoga for people with metastatic cancer and intervention duration in people with localized or regionally advanced cancer requires further study. Hypnosis RCT 9 Anxiety [39][40][41][42][43][44][45] Anxiety and depression 46,47 Mindfulness-based interventions SR 7 Anxiety and depression [48][49][50][51][52][53][54] RCT 7 Depression 55,56 Anxiety and depression [57][58][59][60][61] Music therapy and music-based interventions SR 4 Anxiety and depression [62][63][64][65] RCT 4 Anxiety [66][67][68] Reflexology RCT 9 Anxiety [69][70][71][72] Anxiety and depression [73][74][75][76][77] Relaxation techniques SR 4 Anxiety and depression [78][79][80][81] RCT 5 Anxiety and depression [82][83]…”
Section: Recommendationsmentioning
confidence: 99%
“…In MBCT, elements of cognitive behavioral therapy are combined with mindfulness-based stress reduction (MBSR) [15,16]. Studies have demonstrated that MBCT is bene cial for mitigating psychological distress in individuals with cancer [17][18][19][20][21][22]. Face-to-face group MBCT and one-on-one Internet-based MBCT are equally e cacious in reducing psychological distress among breast cancer patients.…”
Section: Introductionmentioning
confidence: 99%